Answer:
h = -6
Step-by-step explanation:
Use the quadratic formula
ℎ
=
−
±
2
−
4
√
2
h=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}
h=2a−b±b2−4ac
Once in standard form, identify a, b, and c from the original equation and plug them into the quadratic formula.
ℎ
2
−
3
6
=
0
h^{2}-36=0
h2−36=0
=
1
a={\color{#c92786}{1}}
a=1
=
0
b={\color{#e8710a}{0}}
b=0
=
−
3
6
c={\color{#129eaf}{-36}}
c=−36
ℎ
=
−
0
±
0
2
−
4
⋅
1
(
−
3
6
)